Effects of tillage and seeding methods on soil physical properties and yield of upland rice for an ultisol in southeast Nigeria - Ogunremi, L.T.; Lal, R.; Babalola, O. (1986)
The yield of direct-seeded and transplanted upland rice was investigated for seven tillage methods for an ultisol in a high rainfall region of southeastern Nigeria. The tillage methods were: two compaction passes of a 6-t roller with and without residue mulch; six compaction passes with mulch; ploughing with and without mulch and no-till with and without mulch. Soil compaction decreased seedling emergence and shoot and root growth. Residue mulching decreased seedling emergence by 35.6% in direct-seeded rice. There were more leaves, productive tillers and dry matter in the ploughed plots. Root densities at 10–20- and 20–30-cm depths were higher by 157 and 47%, respectively, in ploughed treatments. The highest grain yields of 6.3 and 6.1 Mg ha−1 in ploughed plots for the first and second seasons, respectively, were associated with greater uptake of P, Na, Fe and Zn at flowering and of N, Mg, K, Mn and Cu at both maximum tillering and flowering growth stages. The grain yield in the first season was 2.1 and 2.5 Mg ha−1 for two- and six-compaction pass mulched plots, respectively. In the second season, the yields of no-till and compacted treatments were identical and ranged from 1.5 to 2.4 Mg ha−1. Mulching decreased grain yield by 43, 27 and 12% on compacted, no-till and ploughed plots, respectively, due to transient flooding and mechanical impedance to seedling emergence by the mulch cover. Within the unmulched treatments, ploughing increased rice yield by 71 and 35% over two compaction passes and the no-till treatments, respectively. The least bulk density and penetrometer resistance were also observed in ploughed plots.